Get Jailed, Jump Bail? The Impacts of Cash Bail on Failure to Appear and re-Arrest in Orleans Parish - Monaghan, Jake (American journal of criminal justice, 2022)
Cash bail has come under increasing scrutiny because of the high number of defendants who remain detained pretrial when they are unable to afford their release. According to critics, this amounts to punishment on the basis of poverty, not crime. As a result, releasing defendants on their own recognizance (ROR) is becoming an increasingly popular reform implemented by cities and states. In this paper, we study individuals released pretrial by Orleans Parish Sheriff’s Office between December 2018 and November 2019 to understand the role and impacts of cash bail and ROR on failure to appear (FTA) and re-arrest rates. We find that ROR does not increase an individual’s likelihood of FTA, but drug tests, a common condition attached to ROR, do increase the chances of FTA. Additionally, larger cash bail amounts and longer times spent awaiting release are correlated with increased rates of re-arrest. We also find substantial disparities in pre-release conditions based on a defendant’s race. These results indicate that reducing or eliminating cash bail will not have a substantial impact on public safety and may have other benefits associated with justice and equity.